The Miracle of the Prophet Jonah in the Belly of a Whale Relevance of Qs. Al-Anbiya Verses 87-88 I'Jaz Ghaibi's Perspective - Dinda Kartika; Fikri Hidayat El Izat (Penerbit Hellow Pustaka, 2026)
The story of the Prophet Yunus 'Alaihissalam in the Al-Qur'an surah QS. Al-Anbiya verses 87–88 contain spiritual lessons as well as showing the miracle of revelation. This research aims to analyze the miracle of the Prophet Yunus in the belly of a fish through the perspective of i'jaz ghaibi using literature study methods, thematic interpretation and balAghah analysis. The results of the study show that this verse contains supernatural miracles through the description of the condition of the Prophet Jonah in various darkness, prayers offered in secret, and the certainty of God's help. Apart from that, the beauty of the language of the Koran is visible through its concise and profound style of expression. This story also emphasizes the value of patience, repentance and submission to Allah and is a lesson for all believers.